Students' Mathematic Reasoning: a Review from Jigsaw and ROPES Learning Model at Baiti Jannati Junior High School - Mara Samin Lubis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The background of this article is that the learning carried out by the teacher in the classroom only focuses on the teacher, the class condition is not effective. This study aims to see the difference between the mathematical reasoning of students who are taught using the jigsaw learning model and the ROPES (Review, Overview, Presentation, Exercise) learning model in class VIII SMP Baiti Jannati on Prisma material. This research is a quantitative research that uses the entire population of class VIII with a sample of class VIII-1 and VIII-2 with a total of 30 students in each class. This study uses a one-way ANOVA test using a description test. Based on the results of this study indicate that there is a difference between the jigsaw and ROPES learning models with Fcount Ftable; 26.89 4.07. The mathematical reasoning of students reviewed using the jigsaw learning model is better than the mathematical reasoning of students reviewed using the ROPES learning model on Prisma material in class VIII SMP Baiti Jannati.